Urinary electrolyte parameters in sepsis-associated acute kidney injury: A prospective observational study - Rajathadri Hosur Ravikumar; Anjan Trikha; Rashmi Ramachandran; Sudip Kumar Datta; Mrudula Prasanna; Vimi Rewari (Indian Journal of Anaesthesia)
Background and Aims: Sepsis-associated acute kidney injury (SA-AKI) significantly contributes to morbidity and mortality. Current biomarkers have limitations, necessitating the exploration of alternative indicators. This study aims to evaluate various urinary electrolyte parameters to predict SA-AKI. Methods: A prospective observational study included 111 sepsis patients within 24 h of admission. Urinary electrolyte samples were collected, and indices were calculated. Patients were monitored for 7 days to assess for acute kidney injury (AKI) according to Kidney Disease Improving Global Outcomes (KDIGO) definition criteria, mortality rates, and the need for renal replacement therapy. Mann-Whitney U test and Chi-squared test were used to analyse continuous and categorical variables, respectively. Receiver-operating characteristic (ROC) curves were constructed to determine to discriminatory ability of various parameters in predicting AKI. Results: Of 111 patients, 42.3% developed AKI, with a mortality rate of 59.5%. When evaluating urinary parameters, the product of urine sodium and urine creatinine exhibited the maximum full form [area under the receiver operating characteristic (AUROC): 0.66; 95%CI: 0.56, 0.77)], and the parameter of fractional excretion of potassium (FeK) exhibited an AUROC of 0.62 (95%CI: 0.51, 0.72). Furthermore, 2-hour excretion of potassium revealed a statistically significant correlation with 2-hour creatinine clearance (r = 0.62, P < 0.001). Logistic regression models, incorporating Sequential Organ Failure Assessment (SOFA) score, FeK, and urine sodium concentration as variables (P = 0.020, 0.044, and 0.033, respectively), achieved an AUROC of 0.751 in predicting AKI. Conclusion: Urine sodium levels and fractional potassium excretion moderately effectively predict AKI in sepsis patients. Urine potassium excretion correlates with glomerular filtration rate.